Islamic Philantrophy Development in Digital Era: New Strategy of Fund Raising and Supervision Program - Efendi, Mansur; Arifin, Ferdi (BISNIS, 2019)
Industry 4.0, which is a shape of fourth stage of industrial revolution, influences human life such as new media development. Nowadays, most people are being active users in digital world as a new social sphere. Many activities in social media affects various creative ideas, one of them is a medium of fund raising. As fourth stage of industrial revolution it does not cut off humanitarian acts for caring each others, even its appearance can be alternative media to create various humanitarian acts. Islamic philantrophy has take for granted New Media as developing model of fund raising and supervision program to enhance humanitarian acts. This study attempts to analyze developing of Islamic philantrophy phenomena in new media by utilizing qualitative method. The results is going to find a model of fund raising throughout new media and to create a program of supervision for sustainability acts as an effort to establish prosperous society. By this research, Islamic philantrophy is able to develop rapidly and achieve wider success through a new strategy. The main aspect of new strategy model must be syncronized to Islamic laws embedded in Quran and Hadits for avoiding inappropiate ways and debatable rules.